A Schumpeter-inspired approach to the construction of R&D capital stocks - Jürgen Bitzer; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
A new method for constructing R&D capital stocks is proposed. Following Schumpeter, the development of R&D capital stocks is modelled as a process of creative destruction. Newly generated knowledge is assumed not only to add to the existing R&D capital stocks but also, by displacing old knowledge, to destroy part of that capital. This is in stark contrast to the perpetual inventory method, which postulates a constant rate of depreciation. We compare both methods by estimating the impact of R&D and spillovers on output in OECD countries, and find that the new approach leads to more sensible and robust results.
Keywords: C82; O31; D62; 330; R&D capital stocks; knowledge spillovers; creative destruction; Forschung; Gesamtwirtschaftliches Anlagevermögen; Spillover-Effekt; Schumpeterismus; Schätztheorie; Theorie